Peran Masyarakat dalam Meningkatkan Kinerja Pemerintahan Desa di Desa Bandar Setia Kecamatan Percut Sei Tuan - Eunike Br Simanjuntak; Julia Ivanna (Departement of Mathematics Education, 2024)
This research aims to explore the role of the community in enhancing the performance of the government in Bandar Setia Village, Percut Sei Tuan Subdistrict. The research method employed is qualitative with data collection techniques through interviews and observations. The results indicate that the community's role in enhancing the performance of village governance is crucial. The community actively participates in oversight, policy-making, and provides feedback and suggestions to the village government. Collaboration between the village government and the community has positive impacts on village development and management. However, several challenges are identified, such as a lack of community participation awareness and local-level conflicts of interest. Therefore, greater efforts are needed to enhance community involvement so that the performance of village governance can be continually improved to achieve sustainable development in Bandar Setia Village.